Stability analysis of tunnel in sandy cobble strata under different pre-reinforcement techniques - Li, Xiaobin; Zhao, Ying; Xue, Haifang; Zhang, Lei; Gong, Xiaoqin (Frontiers in Earth Science, 2023)
Excavating tunnels in sandy cobble strata carries a high risk of ground collapse caused by instability of the tunnel face. In order to prevent instability at the tunnel face during excavation, this paper focuses on studying the effects of various pre-reinforcement method on the stability of tunnel in the sand-cobble strata. Firstly, pre-reinforcement projects suitable for these tunnels are proposed. Then, using FLAC3D to established numerical models, then simulate the excavation process under six different working conditions: non-reinforced, pre-reinforcement with advance small pipes, pre-reinforcement with pipe-roof, pre-reinforcement with GFRP bolts, pre-reinforcement with advance small pipes and GFRP bolts, and pre-reinforcement with pipe-roof and GFRP blots. The displacement and stress fields of the soil behind and in front of the tunnel face under each condition are obtained. The results show that the use of GFRP bolts for pre-reinforcement can effectively control the deformation of the surrounding rock in front and behind the tunnel face, and pre-reinforcement with advance small pipes or pipe-roof can reduce the settlement of the tunnel crown. Pre-reinforcement by the combination of GFRP bolts with advance small pipes or pipe-roof can better ensure the stability of the tunnel during the excavation process.